In vitro effects of intravenous propofol infusion on cytokine gene expression in rats - (:unkn) unknown (My University, 2008)
Objective: The aim of this study was to evaluate the effects of propofol infusion on cytokine gene expression levels of bone marrow and mesentheric lymph nodes in rats after surgical trauma. Methods: Twenty male Sprague-Dawley rats weighing between 300-320 g were divided into two groups (n=10). Midline laparotomy incision was performed on both groups. Group I received 5 ml/kg/hr iv serum physiologic infusion. Group II received 5 mg/kg/hr iv propofol infusion. After infusion, mesentheric lymph node and bone marrow samples were obtained for the measurement of IL-1, IL-6 and TNFα gene expression levels by real time polymerase chain reaction (RT-PCR) method. Results: IL-1 (p<0.002) and TNFα (p<0.018) levels of the mesentheric lymph node were significantly lower in group II compared to group I. TNFα gene expression level in the bone marrow was also significantly lower in group II compared to group I (p<0.0015). Conclusion: Propofol infusion during surgery caused significantly more proinflammatory cytokine gene expression supression in the mesentheric lymph nodes compared to bone marrow in rats. We concluded that propofol infusion may have a limited and especially local immune supressive effect.
Keywords: Anesthesia; Cytokine; Gene expression; Immune system; Propofol